LEAKAGE FAILURE ANALYSIS OF TUBE BUNDLE CONNECTION OF FLUE GAS WASTE HEAT RECOVERY DEVICE (MT) - REN ZiQi; DONG JinShan; FENG Jun; DING Yi (Jixie qiangdu)
Leakage occurred on a company′s waste heat recovery unit after short-term operation of it. In order to determine the cause of the leak and take effective countermeasures, the reasons for the failure of the waste heat recovery device were analyzed. Firstly, the stress level of the waste heat recovery device under working condition was calculated by Ansys simulation software, and the maximum stress point was found at the tube sheet, and the stress value at the joint of tube sheet and heat exchange tube was larger.Then, macro-corrosion morphology analysis, metallographic microstructure analysis, micro-hardness test, scanning electron microscope（SEM） analysis of corrosion micro-morphology and EDS micro-area composition analysis of corrosion products were carried out on the sampling site of tube bundle leakage.The results show that, because of high temperature, increasing alkali concentration occurs at the crack of tube bundle. And welding cracks exist there, which eventually leads to alkali stress corrosion cracking at the weld of tube sheet and tube bundle.